Brown glass for gallon bottle and preparation method thereof
Patent Information
- Application Number
- CN202411336506.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-28
AI Technical Summary
Existing glass materials are difficult to meet the needs of high UV barrier, chemical stability and mechanical strength in gallon bottle applications.
By carefully designing the ingredient ratio and granularity level of the glass, using SIO2, Al2O3, CACO3, MGO, K2CO3, Na2CO3, Fe2O3, C and NA2SO4 and other raw materials to prepare brown glass with excellent ultraviolet blockage, chemical stability, and mechanical strength Essence
The high -ultraviolet barrier, chemical stability, and mechanical strength of gallon bottle with brown glass meet the performance indicators of gallon bottle.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special glass manufacturing and relates to brown glass for gallon bottles and a preparation method thereof. Background Art
[0002] The gallon bottle originated in the United States in the 1970s. Its original capacity was one-fifth of a gallon (about 757 ml), but was later unified to the international standard of 750 ml. Made through high-temperature melting, forming and cooling processes, the gallon bottle is widely used in liquid packaging, especially alcoholic beverages; and the brown gallon bottle is made through a special formula. It is not only beautiful, but also can effectively block ultraviolet rays, and is suitable for liquids that need to be stored away from light.
[0003] Although existing glass materials can provide certain UV protection, they still need to be improved to meet the special requirements of gallon bottles, such as high UV blocking, good chemical stability and mechanical strength. Therefore, it is urgent to develop a new glass material that can meet these specific indicators. Summary of the invention
[0004] The purpose of the present invention is to make up for the shortcomings of the prior art and provide a brown glass for gallon bottles and a preparation method thereof. The present invention can produce brown glass for gallon bottles with excellent ultraviolet barrier properties, chemical stability and mechanical strength by carefully designing the glass proportion and particle size grading.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A brown glass for gallon bottles, characterized by being made of the following raw materials in percentage by weight: SiO2 (60-65 wt%), Al2O3 (1-3 wt%), CaCO3 (8-16 wt%), MgO (0.1-1 wt%), K2CO3 (0.5-2.5 wt%), Na2CO3 (10-18wt%), Fe2O3 (0.14-0.8wt%), C (0.3-0.9 wt%), Na2SO4 (0.1-2wt%), wherein SiO2 is introduced in the form of silica sand, and the particle size of the silica sand is 60~80 mesh.
[0006] Furthermore, the moisture content of each raw material is between 0 and 0.5%.
[0007] The weight percentages of the above components are accurately calculated to meet the specific performance requirements of the gallon bottle, and the particle size of the silica sand is strictly controlled within the range of 60-80 meshes, so as to help obtain a uniform melt more quickly during the melting process and improve the strength and thermal stability of the glass. In addition, the present invention also strictly controls the moisture content of the raw materials within the range of 0-0.5% to reduce the generation of bubbles during the melting process and improve the transparency and uniformity of the glass. These technical measures together ensure that the brown glass produced by the present invention can meet the various performance indicators of the gallon bottle.
[0008] Furthermore, the brown glass batch material for gallon bottles with silica sand particle size distribution is characterized by being made of the following raw materials in percentage by weight: SiO2 (60-61 wt%), Al2O3 (1.2-2 wt%), CaCO3 (15-16 wt%), MgO (0.3-0.5 wt%), K2CO3 (1-1.5 wt%), Na2CO3 (15-18wt%), Fe2O3 (0.14-0.18wt%), C (0.3-0.6 wt%), and Na2SO4 (0.3-0.65 wt%), wherein SiO2 is introduced in the form of silica sand having a particle size of 66-75 mesh.
[0009] A method for preparing brown glass for gallon bottles, characterized by comprising the following steps: (1) Weighing the raw materials according to the above weight percentages and mixing them evenly to obtain a mixed material; (2) The mixed material is placed in a furnace for melting. A specific temperature regime is adopted during the melting process: first, the furnace temperature is raised to 900°C, and then the batch material is placed in the furnace and kept for 0-0.5 hours; then the temperature is raised from 900°C to 1050-1150°C for 0.5-1 hour; then the temperature is gradually raised from 1050°C to 1400-1500°C for 1.5-2 hours, and kept at this temperature for 0.5 to 1 hour to obtain a uniform glass liquid; (3) Pour the molten glass directly onto the copper mold for molding to ensure the stability of the molding process and the shape accuracy of the glass; (4) The formed glass sample is immediately placed in a muffle furnace at 500-550°C for annealing and kept warm for 0.5-1 hour to ensure that the stress inside the glass is released and to improve the mechanical strength and stability of the glass; the glass sample is then cooled to room temperature in the furnace; (5) Finally, the glass sample is subjected to post-processing steps such as cutting, grinding and polishing to obtain brown glass for gallon bottles.
[0010] Beneficial effects of the present invention: 1. The present invention uses low-aluminum soda-lime-silica glass (soda-lime-silica glass has the advantages of low melting point and easy processing) as the basic formula. A small amount of aluminum oxide is added to increase the strength of the glass without increasing the melting point too much, so that the processing performance and use performance of the glass are balanced. Iron oxide, sodium sulfate and carbon powder are used as colorants for the glass, so that a relatively pure brown color can be obtained without changing the mechanical properties of the glass. At the same time, sodium sulfate and carbon powder also have the function of clarifiers, which can make the glass easier to clarify and uniform. 2. Since the mirabilite and carbon powder are used as both colorants and clarifiers, they will continue to volatilize at high temperatures, and the valence state of the iron element in the glass will change with the redox atmosphere, thereby causing the color of the glass to change. Therefore, the melting time of the glass cannot be too long, otherwise the mirabilite and carbon powder will volatilize too much, causing the glass to turn green. If the melting time is too short, the glass clarification effect will be poor, resulting in defects such as bubbles and unevenness in the glass. Therefore, after many experiments, the temperature system of the present invention is the most suitable; 3. The transmittance of 3mm thick gallon bottles made of brown glass was tested, and the average transmittance in the wavelength range of 400~760nm was 52-72%, the compressive strength was greater than 0.28MPa, the mechanical impact strength was 0.1-0.12J, and the surface alkali dissolution was 0.1-0.12ml. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a picture of the glass sample melted in Example 1; Figure 2 This is a glass sample diagram melted from Example 2; Figure 3 This is a picture of the glass sample melted in Example 3; Figure 4 This is a picture of the glass sample melted in Example 4; Figure 5 This is a glass sample image melted from Comparative Example 1; Figure 6 This is a glass sample image melted from Comparative Example 2; Figure 7 This is a picture of the glass sample melted in Comparative Example 3. DETAILED DESCRIPTION
[0012] A method for preparing brown glass for gallon bottles, the specific implementation steps are as follows: Example
[0013] 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.64% Al2O3, 1.52% dolomite, 16% calcite, 17.6% Na2CO3, 1.46% K2CO3, 0.5% Na2SO4, 0.33% C, and 0.15% Fe2O3. The moisture content of the raw materials is less than 0.1%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.35-0.425mm; 2. Load the prepared raw materials into a double-roll mixer for mixing. Mix the raw materials for 1 hour to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1450°C for 2 hours, and keep it warm for 0.5 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 1 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 52.33%, the compressive strength was greater than 0.29MPa, the mechanical impact strength was greater than 0.1J, and the surface alkali dissolution was less than 0.1ml. Example
[0014] 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.82% Al2O3, 16.64% CaCO3, 0.33% MgO, 17.8% Na2CO3, 1.46% K2CO3, 0.5% Na2SO4, 0.5% C, and 0.15% Fe2O3. The moisture content of the raw materials is less than 0.1%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.35-0.425mm; 2. Load the prepared raw materials into a double-roll mixer for mixing. Mix the raw materials for 1 hour to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1450°C for 2 hours, and keep it warm for 0.5 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 2 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 60.09%, the compressive strength was greater than 0.3MPa, the mechanical impact strength was greater than 0.12J, and the surface alkali dissolution was less than 0.11ml. Example
[0015] 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.64% Al2O3, 1.52% dolomite, 16% calcite, 17.6% Na2CO3, 1.46% K2CO3, 0.33% Na2SO4, 0.33% C, and 0.15% Fe2O3. The moisture content of the raw materials is less than 0.1%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.35-0.425mm; 2. Load the prepared raw materials into a double-roll mixer for mixing. Mix the raw materials for 1 hour to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1450°C for 2 hours, and keep it warm for 0.5 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 3 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 68.15%, the compressive strength was greater than 0.28MPa, the mechanical impact strength was greater than 0.12J, and the surface alkali dissolution was less than 0.1ml. Example
[0016] 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.64% Al2O3, 1.52% dolomite, 16% calcite, 17.6% Na2CO3, 1.46% K2CO3, 0.5% Na2SO4, 0.33% C, and 0.16% Fe2O3. The moisture content of the raw materials is less than 0.1%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.35-0.425mm; 2. Load the prepared raw materials into a double-roll mixer for mixing. Mix the raw materials for 1 hour to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1450°C for 2 hours, and keep it warm for 0.5 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 4 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 71.74%, the compressive strength was greater than 0.29MPa, the mechanical impact strength was greater than 0.11J, and the surface alkali dissolution was less than 0.12ml.
[0017] Comparative Example 1: 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.64% Al2O3, 1.52% dolomite, 16% calcite, 17.6% Na2CO3, 1.46% K2CO3, 0.5% Na2SO4, 0.33% C, and 0.15% Fe2O3. The moisture content of the raw materials is less than 0.1%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.125-0.15mm; 2. Load the prepared raw materials into a double-roll mixer for mixing. The mixing time is controlled within 1 hour to ensure that the raw materials are mixed evenly to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1450°C for 2 hours, and keep it warm for 0.5 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 5 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 81.96%, the compressive strength was greater than 0.25MPa, the mechanical impact strength was greater than 0.1J, and the surface alkali dissolution was less than 0.1ml.
[0018] Comparative Example 2: 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.64% Al2O3, 1.52% dolomite, 16% calcite, 17.6% Na2CO3, 1.46% K2CO3, 0.5% Na2SO4, 0.33% C, and 0.15% Fe2O3. The moisture content of the raw materials is less than 0.1%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.35-0.425; 2. Load the prepared raw materials into a double-roll mixer for mixing. The mixing time is controlled within 1 hour to ensure that the raw materials are mixed evenly to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1550°C for 2 hours, and keep it warm for 2 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 6 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 87.704%, the compressive strength was greater than 0.25MPa, the mechanical impact strength was greater than 0.09J, and the surface alkali dissolution was less than 0.2ml.
[0019] Comparative Example 3 1. The ingredients are prepared according to the mass percentage of 60.8% SiO2, 1.64% Al2O3, 1.52% dolomite, 16% calcite, 17.6% Na2CO3, 1.46% K2CO3, 0.5% Na2SO4, 0.33% C, and 0.15% Fe2O3. The moisture content of the raw materials is 8%, and the silicon dioxide is selected from silica sand particles with a particle size of 0.35-0.425mm; 2. Load the prepared raw materials into a double-roll mixer for mixing. The mixing time is controlled within 1 hour to ensure that the raw materials are mixed evenly to obtain a uniform mixture; 3. Melt the mixture obtained in step 2 in a furnace: heat the furnace from room temperature to 900°C, put the batch material into it, and then heat it to 1100°C for 0.5h; then heat it from 1100°C to 1450°C for 2 hours, and keep it warm for 0.5 hours to obtain glass liquid; 4. The melted glass liquid enters the tin bath and is cast by the iron plate casting method, such as Figure 7 As shown; 5. The formed glass samples were annealed in an annealing kiln and kept at 550°C for 0.5h. The glass samples were cooled to room temperature along with the furnace and then cut and polished to obtain 3mm thick glass sheets. The transmittance test showed that the average transmittance in the wavelength range of 400~760nm was 78.074%, the compressive strength was greater than 0.20MPa, the mechanical impact strength was greater than 0.06J, and the surface alkali dissolution was less than 0.1ml.
[0020] Table 1
[0021] The difference between the above four embodiments and comparative example 1 is that the embodiment uses the same silica sand particle size grading, but the ratio of the colorant is slightly adjusted within the range. The difference from comparative example 2 is the different melting temperature and time. The difference from comparative example 3 is that the moisture content of the raw material is less. The oxide composition and the ratio of the colorant in the comparative example are unchanged, but the particle size of the silica sand is smaller than that used in the embodiment. The melting temperature and melting time of comparative example 2 are higher, and the moisture content of the raw material of comparative example 3 is too high. As a result, the color of the glass in comparative example 1 is obviously green, the color of the glass in comparative example 2 is too light, and the transmittance is also higher, and it cannot effectively block ultraviolet rays. The glass in comparative example 3 has many stripes inside, which is very uneven, and the mechanical strength and chemical stability are reduced, which does not meet the use requirements of the gallon bottle. The glass samples in the embodiments are all brown to dark brown, which can block most ultraviolet rays and meet the use requirements of the gallon bottle.
[0022] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form; any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A brown glass for gallon bottles, characterized in that It is made of the following raw materials in weight percentage: SiO2 60-65wt%, Al2O3 1-3 wt%, CaCO3 8-16 wt%, MgO 0.1-1 wt%, K2CO3 0.5-2.5 wt%, Na2CO3 10-18wt%, Fe2O3 0.14-0.8wt%, C 0.3-0.9 wt%, Na2SO4 0.1-2 wt%, wherein SiO2 is introduced in the form of silica sand, and the particle size of the silica sand is 60~80 meshes.
2. The brown glass for gallon bottles according to claim 1, characterized in that: The moisture content of each raw material is between 0 and 0.5%.
3. A brown glass for gallon bottles according to claim 1 or 2, characterized in that It is made of the following raw materials in weight percentage: SiO2 60-61 wt%, Al2O3 1.2-2 wt%, CaCO3 15-16 wt%, MgO 0.3-0.5 wt%, K2CO3 1-1.5 wt%, Na2CO3 15-18 wt%, Fe2O3 0.14-0.18 wt%, C 0.3-0.6 wt%, Na2SO4 0.3-0.65 wt%, wherein SiO2 is introduced in the form of silica sand, and the particle size of the silica sand is 66-75 meshes.
4. A method for preparing brown glass for gallon bottles according to claim 1 or 2, characterized in that The steps include: (1) Weighing the raw materials according to the above weight percentages and mixing them evenly to obtain a mixed material; (2) The mixed material is placed in a furnace for melting. A specific temperature regime is adopted during the melting process: first, the furnace temperature is raised to 900°C, and then the batch material is placed in the furnace and kept for 0-0.5 hours; then the temperature is raised from 900°C to 1050-1150°C for 0.5-1 hour; then the temperature is gradually raised from 1050°C to 1400-1500°C for 1.5-2 hours, and kept at this temperature for 0.5 to 1 hour to obtain a uniform glass liquid; (3) Pour the molten glass directly onto the copper mold for molding to ensure the stability of the molding process and the shape accuracy of the glass; (4) The formed glass sample is immediately placed in a muffle furnace at 500-550°C for annealing and kept warm for 0.5-1 hour to ensure that the stress inside the glass is released and to improve the mechanical strength and stability of the glass; the glass sample is then cooled to room temperature in the furnace; (5) Finally, the glass sample is processed through cutting, grinding and polishing to obtain brown glass for gallon bottles.
5. The brown glass for gallon bottles according to claim 1 or 2, characterized in that: The transmittance test of 3mm thick gallon bottles made of brown glass showed that the average transmittance in the wavelength range of 400~760nm was 52-72%, the compressive strength was greater than 0.28MPa, the mechanical impact strength was 0.1-0.12J, and the surface alkali dissolution was 0.1-0.12ml.
Citation Information
Patent Citations
Brown glass and uses thereof
CN101428969A
Method for preparing medicinal brown bottle by using cullet
CN101456671A
Formula and preparation method for first-level waterproof glass molding injection bottle glass
CN103058514A
Colored glass plate and method for manufacturing same
CN106232545A
Silica sand grain graduation non-alkali glass batch
CN108483901A